Magnetic Micro and Nanorobot Swarms: From Fundamentals to Applications - Zhang, Li; Yang, Shihao; Wang, Qianqian; Jin, Dongdong (Springer Tracts in Electrical and Electronics Engineering, 2023)
XIV, 349 p. 259 illus., 242 illus. in color.